Utilization of a Novel Rib Spreader for Minimally Invasive Lung Transplantation. (April 2015) - Mohite, Prashant Nanashaeb; Popov, Aron-Frederik; Sabashnikov, Anton; Weymann, Alexander; Simon, Andre R.
Rack-and-pinion-type stainless steel rib spreader was innovated by Truffier in 1914, which was modified by Finochietto to have fenestrated blades and a hand-cranked lever to both separate the arms in a staged fashion and lock them in place at each stop. Its Burford–Finochietto variants with replaceable blades are ubiquitous in open thoracic surgery. Fehling Surgical Instrument, Inc (Acworth, GA) introduced a modified rib spreader—an assembly of movable and adjustable blades, a mobile bridge and spreader arms, which owing to its adaptation of thoracotomy incision provides an optimum exposure without injuring the ribs. The spreader is indispensible in lung transplantation surgery performed especially through minimally invasive (bilateral limited anterolateral thoracotomies with intact sternum) approach.